Review on Advances in Pediatric Endoscopy in the Management of Inflammatory Bowel Disease - Isoldi, Sara; Mallardo, Saverio; Quitadamo, Paolo; Leter, Beatrice; Cucchiara, Salvatore (Current Pediatric Reviews, 2025)
Over the past decades, an increased importance has been given to gastrointestinal (GI) endoscopy in the management of children with inflammatory bowel diseases (IBD), considering that mucosal healing has been recognized as the optimal endpoint in the treat-to-target paradigm. The recent advances in technology and anesthesia have facilitated the comprehensive evaluation of the GI tract. In this review, we will discuss the role of ileocolonoscopy, upper GI endoscopy, and device-assisted enteroscopy in the work-up and management of pediatric Crohn’s disease (CD) and ulcerative colitis, with particular attention on non-invasive endoscopic techniques, such as wireless capsule endoscopy. We will also analyze the most commonly used endoscopic scoring systems, including small bowel scoring systems and endoscopic recurrence grading of neo-terminal ileum CD. Moreover, we will focus on the endoscopic management of complications, such as strictures, that commonly require surgery. Lastly, we will discuss cancer surveillance in children with IBD, with particular consideration of the role of high-definition endoscopic equipment and chromoendoscopy in dysplasia detection rates.
Keywords: pediatrics